The Chemical Composition of Ground Water in Observational Water Vents in the Petropavlovsk Geodynamic Test Site: The Classification and Effects of Large Earthquakes - Kopylova G.N.; Guseva N.V.; Kopylova Yu.G.; Boldina S.V. (Journal of Volcanology and Seismology, 2018)
This paper considers the chemical composition and classification of ground water at seven flowing wells and four springs using materials from the 2014 hydrogeochemical sampling and from continuous observations conducted by the Kamchatka Branch of the Geophysical Survey of the Russian Academy of Sciences (KB GS RAS) in 1989–1999. We estimated the saturation of ground water discharges at individual vents with alumosilicate, carbonate, and sulfate secondary minerals, following the behavior of saturation over time. We have found that the ground water undergoes an increase in the saturation with secondary minerals during large earthquakes that produced shaking of intensity I = 5–6 on the MSK-64 scale. Such changes in the saturation of ground water with secondary minerals are less pronounced during the precursory periods before earthquake occurrence. We discuss desirable future developments of the observational system at wells and springs in order to look for new types of hydrogeochemical precursors to earthquakes.